Analisis Perbandingan Layout Form Single-Page dan Multi-Page dalam Pengisian Form Data Penduduk - Muhammad Satrio Bayu Pamungkas; Muhammad Aminul Akbar; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Population data is very important for the life of the state, because population data is needed for various kinds of government administration services. One source of population data itself is from population data registration. With the development of information technology in Indonesia, registration of population data that was previously done manually can now be done digitally. Then to be able to meet these needs, an online form or web form is needed. Until now there are various types of forms that can be used according to these needs. Several types of forms that are commonly used on various websites today are single-page and multi-page forms. Single-page has the advantage of being easy to check data entries. Multi-page has the advantage of dividing data entry into several parts so filling out the form doesn't feel long and tiring. With each of these advantages, this research focuses on a comparative analysis between single-page and multi-page forms on time efficiency in filling in population data. Comparisons were made using normality tests and parametric comparison tests to determine differences between the two types of forms. The calculation results show that there is a difference between single-page and multi-page designs in terms of time efficiency which leads to multi-page forms whose average time efficiency is better than single-page.